(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Different generations have stepped into the 21st century with different life experience, which led to discrepancies in cultural and symbolic space of collective memory. The feeling of social space and historical time, which is specific for each of the living generations, has a peculiar reflection in the policies of memory, which development is influenced by both objective and subjective factors. Assessing the level of conflict between generations, and its relationship with politics of memory, we can talk about the different dimensions of stratification of life experience typical for the major age groups. The most important events of history that do not intersect in general axiological space get recorded in the collective consciousness of the living generations. Among those are the World War II, the post-war years followed by the Cold War, Gorbachev’s perestroika and the collapse of the Berlin Wall, the collapse of the Soviet Union and the collapse of the bipolar world, the formation and establishment of an independent post-soviet states. The social changes that have taken place in a relatively short historical period set the scientific community of the post communist countries before the need to reflect on the politics of memory and the conflict of generations. The research of value-based relationships between generations, as well as issues of historical gaps of social time and their influence on the politics of memory are on the agenda as well.